Development of Novel RP-HPLC and Chromogenic UV-Visible Methods for the Estimation of Sitagliptin Using NQS in Bulk and Biological Samples in Compliance with ICH M10 and Q2(R2) Guidelines - Sri, Khagga Bhavya; Keerthana, Tailors; Pravallika, Jinkala; Sumakanth, Mogili (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim: This study develops and validates two analytical methods: An innovative UV-visible chromogenic spectrophotometric method applied to bio-samples and a (RP-HPLC) High-performance liquid chromatography method in reversed phase to measure sitagliptin in pure and pharmaceutical formulations in compliance with M10 and ICH Q2(R2) criteria. Materials and Methods: Method utilizes a chromogenic reaction, where 1,2-naphthoquinone-4-sulfonate was prepared and optimized as the chromogenic reagent. This reagent reacted with sitagliptin under controlled pH and temperature to produce a coloured product. The resultant chromogen's absorbance was measured spectrophotometrically at its maximum absorption wavelength. Concentration ranges for RP-HPLC were 25-150 µg/mL. Results: Mobile phase for RP-HPLC was made by combining methanol of HPLC grade with potassium dihydrogen phosphate pH 4.3 in 70:30 ratio, 10 min of run time at a flow rate of 1.2 mL/min. Retention time was recorded at 3.41min. Chromogenic method demonstrated a linear response throughout a specific concentration range. calibration curve equation for chromogenic bioanalytical method at 454nm and y=0.0187x+0.0264, R²=0.9998. 5 µg/mL and 100 µg/mL were found to be the Lower Limit of Quantification (LLOQ) followed by Upper Limit of Quantification (ULOQ), respectively for chromogenic method. Conclusion: Both RP-HPLC and chromogenic UV spectrophotometric methods provide rapid as well accurate quantification of sitagliptin in formulations and bulk drug samples. Protein precipitation extraction method was used to design, validate, and expand improved procedure to biological samples. Validation results support their suitability for routine quality control analysis, offering reliable and efficient tools for sitagliptin quantification.
Keywords: ICH M10 Guideline; ICH Q2R2; NQS Reagent; RP-HPLC; Sitagliptin; Spectrophotometric; Method